Twofold C−H Activation‐Based Enantio‐ and Diastereoselective C−H Arylation Using Diarylacetylenes as Rare Arylating Reagents. Issue 37 (6th August 2021) - Hu, Panjie; Kong, Lingheng; Wang, Fen; Zhu, Xiaolin; Li, Xingwei
Abstract: C−H bond activation has been established as an attractive strategy to access axially chiral biaryls, and the most straightforward method is direct C−H arylation of arenes. However, the arylating source has been limited to several classes of reactive and bulky reagents. Reported herein is rhodium‐catalyzed 1:2 coupling of diarylphosphinic amides and diarylacetylenes for enantio‐ and diastereoselective construction of biaryls with both central and axial chirality. This twofold C−H activation reaction stays contrast to the previously explored Miura–Satoh type 1:2 coupling of arenes and alkynes in terms of chemoselectivity and proceeded under mild conditions with the alkyne acting as a rare arylating reagent. Both C−H activation events are stereo‐determining and are under catalyst control, with the 2 nd C−H activation being diastereo‐determining in a remote fashion. Analysis of the stereochemistry of the major and side products suggests moderate enantioselectivity of the initial C−H activation–desymmetrization process. However, the minor ( R ) rhodium vinyl intermediate is consumed more readily in undesired protonolysis, eventually resulting in high enantio‐ and diastereoselectivity of the major product. Abstract : Rhodium‐catalyzed 1:2 coupling of phosphinamides and diarylacetylenes has been realized for enantio‐ and diastereoselective synthesis of axially chiral biaryls bearing a P‐stereogenic center. The reaction proceeded via twofold C−H bond activation, with the alkynes being an arylating reagent.